Acessibilidade em cinemas digitais: uma proposta de geração e distribuição de libras e autiodescrição - Domingues, Leonardo de Araújo (2015)
People with hearing or visually impairment face many di culties to participate in the social life, to communicate with other people and to access information. Their participation in cinemas, theaters, educational environment, among others, is often limited due to the lack of solutions that enable their interaction and participation. For the deaf, for example, the accessibility resources normally provided at the cinema room is limited to subtitle text format. This is the predominant solution on the current scenario. However, on the other hand, there are some studies that are in progress to try to solve these problems, such as the use of second screen devices to project content with sign language. For the blind, the accessibility problem is further aggravated because currently there are few cinema rooms that o er the resources of audio description. Normally, the blind rely solely on the help of family or friends to narrate the events during the exhibition of the lm. The accessibility point of view, these approaches are considered ine cient, since the deaf, for example, have enough trouble reading and writing in the spoken language of their country. Therefore, to minimize these problems, this paper presents a computational solution capable of automatically generating from the subtitles, video tracks with Brazilan Sign Language (Libras) windows for deaf users, and from the movie script, produce audio description for blind users and distribute such content for users using the second screen devices. Experiments using a prototype showed that the solution has the potential to generate e ciently contents intelligible for this users, increasing your access to this technology type.